Prevalence of sexual disorders in relapsing-remitting multiple sclerosis patients depending on various risk factors - Tetiana Odintsova; Oksana Kopchak (Romanian Journal of Medical Practice, 2024)
Objective. Multiple sclerosis is a perilous, disabling, physically as well as mentally, demyelinating disease of the central nervous system. This work aims to evaluate prevalence of sexual dysfunctions and their correspondence with non- and disease related risk factors, as well as with MRI findings in patients with relapsing-remitting multiple sclerosis. Results. Based on conducted multifactorial analysis, the most prominent risk factor associated with presence of sexual dysfunctions in in patients with relapsing-remitting multiple sclerosis was depression. Sexual dysfunctions are tied to cognitive deficit, in general and in separate domains, particularly in memory, executive functions and language. Considering disease-related agents, sensory and motor deficits are linked to the development of sexual dysfunctions in case of relapsing remitting multiple sclerosis. Among non disease-related factors, unemployment, marital status, level of education and tobacco smoking are affecting sexual dysfunctions’ severity. According to the MRI, frontal lobe and corpus callosum and periventricular area were affected more often comparing to other brain regions in case of sexual dysfunctions. Conclusions. Patients suffering from relapsing-remitting multiple sclerosis encounter secondary and tertiary sexual dysfunctions. Knowing all struggles of MS, patients should be offered more nuanced management options that will improve their quality of life on a deeper level.